A revisão no processo de avaliação da escrita no ensino superior: concepções e representações dos alunos - Maria L. Cabral (Universidade do Minho, 2004)
Part of a larger study on conceptions and representations of university students of the writing process, this text focuses on aspects of the evaluation of the writings produced in academic context. Data was collected with a research instrument specifically built and evaluated for the study. Participants constitute a group of 51 students at the final year of their graduation in Portuguese, Portuguese and English and Portuguese and French, at a Portuguese university. Focusing on three dimensions of the evaluation of writing; 1) responsibility for the evaluation; 2) strategies and criteria of evaluation, and 3) representations of the final product, the text presents the results found on the analysis of the answers of the subjects to 4 open questions of the instrument, administered by the researcher. Findings revealed that subjects, future language teachers, still share traditional conceptions and representations of the evaluation of the writing process.